Clinical Characteristics and Neurological Deficit Profiles of Ischemic Stroke Patients at Dr. Soetomo General Academic Hospital - Salsabil Putri Adelia Febryan; Mohammad Saiful Ardhi; Imam Subadi; Sita Setyowatie (AKSONA, 2026)
Highlight: Ischemic stroke most often occus in men aged 56-70 years. Limb weakness is the most common deficit in stroke patients. Most patients showed moderate neurological deficits based on NIHSS.   ABSTRACT Introduction: Stroke is one of the primary causes of disability and mortality. Its incidence increases with advancing age. Approximately 65% of all strokes are ischemic, which can present with a wide range of symptoms, including hemiparesis, facial palsy, aphasia, and dysarthria. A high score on the National Institutes of Health Stroke Scale indicates greater neurological impairment. The lack of neurological impairment data on ischemic stroke patients in Indonesia makes this study important. Objective: This study aimed to examine the clinical features and neurological impairment profiles of ischemic stroke patients admitted to Dr. Soetomo General Academic Hospital. Methods: This descriptive observational study used a cross-sectional design and secondary data from the medical records of 175 ischemic stroke patients admitted to the neurology ward of Dr. Soetomo General Academic Hospital, Surabaya, between January and June 2024.  Results: There were 175 people who had ischemic strokes; 100 of them were men and 75 of them were women. Among them, 48% were in the 56-70 year age group. Hemiparesis (84.6%) was the most prevalent neurological problem, followed by facial palsy (77.7%), dysarthria (52%), and aphasia (27.4%). Of the individuals with aphasia, 64.6% had global aphasia, 25% had motor aphasia, and 10.4% had sensory aphasia. The NIHSS scores of 50 patients showed 6 mild, 37 moderate, 5 moderate-to-severe impairments, and 2 severe impairments. Conclusion: Ischemic stroke most commonly affected older adults, and males with motor weakness, dysarthria, and aphasia as the main neurological manifestations. These common clinical presentations may facilitate early diagnosis, support comprehensive neurological evaluation, and improve patient management.